On the computational algorithm related to antikeys - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
The keys and antikeys play important roles for the investigation of functional dependency in the relational datamodel. The main purpose of this paper is to prove that the time complexity of finding a set of antileys for a given relation scheme S is exponential in the number of attributes. Some another results connecting the functional dependency are given. Key Word and phrase: Relation, relational datamodel, functionsl dependency, relation scheme, generating Armstrong relation, dependency inference, strong schemen, membership problem, closure, closed set, minimal generater, key, minimal key, antikey.